Kolaborasi BUMDes dan Program CSR dalam Pemberdayaan Masyarakat : Studi pada Petani Kopi di Desa Baloi, Kabupaten Murung Raya - Novri Amdani Saragih; Saputra Adiwijaya; Ida Bagus Suryanatha (Jurnal Manajemen Riset Inovasi, 2026)
This study analyzes community empowerment through the collaboration between the Village-Owned Enterprise (BUMDes) Baloi Usaha Mandiri and the Corporate Social Responsibility (CSR) program of PT Maruwai Coal in developing the local coffee commodity "Kopi Baloi" in Tumbang Baloi Village, Murung Raya Regency. A qualitative case-study approach was applied using the Asset-Based Community Development (ABCD) concept, supported by primary field data triangulated with the company's Social Mapping report and Community Development Master Plan (RIPPM). The findings show that the empowerment rests on five community capitals human, social, physical, financial, and natural which have turned local coffee into value-added products such as Kopi Baloi and the "Baloi's Signature" coffee-leaf tea. However, a gap emerges: bonding social capital is strong, whereas bridging social capital remains weak, reflected in a marketing chain still dominated by local markets and middlemen. The study concludes that sustainability requires strengthening bridging social capital, improving branding and marketing, business-to-business (B2B) and business-to-customer (B2C), and addressing community grievances toward the company.